The Influence Of Medical Service Quality On Patient Satisfaction And Its Impact On Patient Loyalty - Al Maududi, Abul A'la; Jaksa, Suherman (Green Publisher, 2024)
The purpose of this study was to determine and analyze: (1) Service Quality (2) Patient Satisfaction; (3) Patient Loyalty; (4) the effect of Service Quality on Patient Satisfaction; (5) the effect of Service Quality on Patient Loyalty; and (6) the magnitude of the effect of Patient Satisfaction on Patient Loyalty at the General Clinic of Puri Asih Hospital, Karawang Regency. The research methods used in this study were descriptive survey and explanatory survey, the unit of analysis in this study were staff in the General Clinic of Puri Asih Hospital, Karawang Regency with a population of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of research and discussion, it is obtained that the Quality of Service provided is inadequate, Patient Satisfaction is considered quite satisfied, Patient Loyalty is considered quite high, Service Quality affects Patient Satisfaction, Service Quality affects Patient Loyalty and Patient Satisfaction affects Patient Loyalty, between Service Quality and Patient Loyalty satisfaction that affects Patient Loyalty, it turns out that Service Quality has a dominant influence. Since Service Quality has a dominant influence on Patient Loyalty rather than Patient Satisfaction, it is recommended to create a pleasant work atmosphere, so that they are able to work more professionally.